Salicylic acid-independent induction of pathogenesis-related protein transcripts by sugars is dependent on leaf developmental stage - Sonnewald, Uwe; et al. (Febs Letters, 1996)
Soluble sugars have been found to regulate a number of genes involved in functions associated with sink metabolism, defense reactions and photosynthesis, As viruses and pathogens induce the expression of pathogenesis-related (PR) protein genes and have also been reported to lead to localized sugar accumulation in leaves, it was investigated whether a salicylic acid-independent but sugar-dependent pathway for PR-protein gene induction may exist in plant cells, Leaf discs of tobacco plants were floated on different sugar solutions, transcript accumulation and salicylic acid (SA) levels were subsequently determined, PR-Q and PAR-1 transcripts were found to be inducible by glucose, fructose and sucrose, No significant change in SA content could be detected, following incubation, On the other hand, SAR8.2 transcripts were repressed by elevated levels of soluble sugars and sorbitol, respectively, suggesting sensitivity to turgor pressure, Since leaves undergo sink to source transition during growth, sugar responsiveness was investigated in leaves of different developmental stages, Interestingly, induction of PR-Q and PAR-1 by soluble sugars was essentially restricted to fully expanded leaves and was independent of plant age, Induction by salicylate was not confined to the source capacity of a leaf but was dependent on the age of the respective leaf, Repression of transcripts encoding photosynthetic genes (ribulose-1,5-bisphosphate carboxylase/oxygenase (rbcS) and chlorophyll a/b binding protein (cab) by soluble sugars were largely independent from the leaf developmental state, These findings hint to the possibility of salicylic acid-independent defense reactions of plants against pathogens by induction of a set of PR proteins in source leaves, Furthermore, the data suggest different mechanisms for the induction of PR-protein genes and the repression of photosynthetic genes by soluble sugars.
Keywords: pathogenesis-related protein; photosynthetic gene expression; salicylic acid; sugar sensing; tobacco